Transfigurations of Hellenism : aspects of late antique art in Egypt, A.D. 250-700 - Török, László, 1941-2020 (Probleme der Ägyptologie ;, 2005)
This richly illustrated book presents a history of Egyptian late antique-early Byzantine (Coptic) art in its international stylistic, social and intellectual context.